Development of MyFunds for Students in UTHM - Muhammad Aiman Syafiq,; Nurezayana, (Applied Information Technology And Computer Science, 2024)
MyFunds UTHM is a dedicated fundraising system designed exclusively for students and staff at Universiti Tun Hussein Onn Malaysia (UTHM). Traditionally, fundraising activities at the university have relied on social media campaigns. To enhance the process, MyFunds UTHM introduces an integrated application and web-based platform, developed using an object-oriented approach and following the System Development Life Cycle (SDLC) methodology. The primary objective of MyFunds UTHM is to establish a secure and transparent environment by safeguarding donor information, including the precise date and time of donations, while also facilitating effortless categorization of contributions according to campaign types. The system is developed in both application and web-based system, effectively supporting crowdfunding and campaigns organized by various clubs and organizations within the university.